New Brunswick's elders neglected and forgotten - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Vieillir dans l'indifférence et l'indignité au Nouveau-Brunswick - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Pratique # 17 : Les séances de dialogue au Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Santé et mieux-être des élèves francophones au Nouveau-Brunswick (Canada) - Boivin, Nathalie; Foulem, Ghislaine; Desjardins, Isabelle Perron (La Revue de Santé Scolaire et Universitaire, 2025)

Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Lumière sur la réforme du système de santé au Nouveau-Brunswick : évolution, jeux d’acteurs et instruments - Collin, Stéphanie (Presses de l'Université d'Ottawa, 2021)

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

Accès aux services de santé en français et gouverne en réseau : différentes représentations et stratégies d'action - Collin, Stéphanie; Grenier, Gabrielle; McIntyre, Martine; Roy, Shanie (Revue Gouvernance, 2022)
Au Canada, l’enjeu de l’amélioration de l’accès aux services de santé en français, surtout dans les provinces hors Québec, s’inscrit dans des relations complexes entre différents acteurs qui poursuivent des objectifs variés. En 2008, au Nouveau-Brunswick, l’État a remplacé les huit régies régionales existantes par deux nouvelles régies, soit la Régie régionale de la santé A (Réseau de santé Vitalité) et la Régie régionale de la santé B (Réseau de santé Horizon). Plus tard, il a été établi que Vitalité fonctionnerait en français et Horizon en anglais, et que les réseaux assureraient la prestation des services de santé dans la langue officielle du choix des citoyens. Ainsi, l’objectif général de la recherche était de comprendre l’influence des dynamiques entre les acteurs d’une gouverne en réseau sur le traitement de l’enjeu que représente l’accès aux services de santé en français. Une méthode qualitative comprenant notamment des entretiens semi-directifs (n=26) a été retenue. Les résultats montrent que, d’une part, l’offre de services dans la langue du choix des citoyens, qui est conditionnée par le cadre juridique sur les droits linguistiques, pousse les acteurs à mobiliser des stratégies axées sur la qualité et la sécurité. D’autre part, l’accès révèle une dimension symbolique, puisqu’il est associé aux notions d’équité et de gouvernance. L’accès aux services de santé en français est un sujet délicat pour l’État, qui demeure en retrait par rapport à celui-ci. Afin de mieux répondre aux besoins en santé des citoyens, cet acteur doit faire émerger des liens de confiance et formuler des objectifs clairs. Mots-clés : gouverne, réseau, accès, santé, communautés francophones en situation minoritaire, langues officielles

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Le difficile pilotage d’une réforme d’un système de santé : le cas du Nouveau-Brunswick (Canada) - Collin, Stéphanie; Lamothe, Lise (Santé publique, 2020)

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Étude sur la santé mentale et les comportements à risque des jeunes adultes - De Moissac, Danielle; Gueye, Ndeye Rokhaya; Plourde, Vikcie; Arseneau, Jolyève; Levesque, Émilie; Corriveau, Hélène; Goguen, Cynthia; Giasson, Florette (Université de Moncton et Université de Saint-Boniface, 2024)
Les jeunes adultes en milieu postsecondaire vivent une transition de vie importante : une plus grande indépendance, de nouvelles relations interpersonnelles et sociales, des prises de décisions déterminantes et des responsabilités importantes qui peuvent être difficiles à gérer, pour certaines personnes. Ces nombreux changements peuvent déstabiliser un sentiment de bien-être et occasionner des troubles de santé mentale, des comportements à risque et des difficultés académiques. Un sentiment d’appartenance à un groupe identitaire est généralement associé à un sentiment de bien-être psychologique, des relations interpersonnelles satisfaisantes et moins de comportements à risque. Les milieux postsecondaires sont des lieux privilégiés pour le développement de ce sentiment d’appartenance, particulièrement dans les CLOSM. (...) L’objectif principal de l’étude est de mieux connaître l’état de santé mentale et les comportements à risque de la population étudiante en milieux postsecondaires dans les communautés de langue officielle en situation minoritaire dans deux provinces canadiennes. Au moment de la collecte de données, la plupart des activités et des cours en présentiel étaient revenus à un état similaire au contexte prépandémique. Ces objectifs permettront à l’équipe de recherche de produire des données probantes qui informeront les parties prenantes (population étudiante, corps professoral, personnel des services à l’effectif étudiant et personnel administratif) des besoins de la population étudiante. Une stratégie de mobilisation des connaissances accompagne cette étude.

From Policy to Practice: A Qualitative Study on Reforms and Frontline Retention in Healthcare - Dubé, Anik; Collin, Stéphanie; Hakim, Jennifer; Johnson, Claire; Laforest, Marie-Ève; Landry, Michel H.; Lauzier, Martin (INQUIRY: The Journal of Health Care Organization, Provision, and Financing, 2025)
In Canada, healthcare reforms typically aim to improve the quality of care and access while making healthcare systems more efficient. These reforms have led to a 2-level healthcare system consisting of provincial and regional health authorities (RHAs). RHAs are responsible for providing and administering health services within specific territories. One of the 2 language-based RHAs in New Brunswick (NB) operates in French-speaking rural minority communities. This study explored key factors affecting the retention of nurses and physicians within a RHA operating in a language minority context. This descriptive qualitative study explored how macro-level decisions are experienced on the frontlines. Data were collected through semi-structured interviews with 21 physicians and 37 registered nurses, as well as 2 focus groups involving 20 key informants in managerial roles. Thematic analysis was used to identify key themes. Three main factors emerged: organizational accountability and frustration, local autonomy and contextual responsiveness, and a culture of openness and perceived loss of control. These factors are associated with policy changes that affect operational settings and resource distribution within the RHA and influence the retention of nurses and physicians. Stakeholders in health system reforms, including governments and RHAs, must recognize that policy adjustments can have direct implications on everyday care. Participants expressed a growing disconnect from decision-making hierarchies and a perceived loss of control. Both are seen as barriers to delivering quality care. Ensuring adequate support and resources for implementing system-level changes is key to fostering professional engagement and enhancing job satisfaction.

Soins et services pour le maintien à domicile des personnes aînées des communautés francophones en situation minoritaire. - Dupuis-Blanchard, Suzanne (Minorités linguistiques et société, 2024)
L’accès aux soins et aux services à domicile en français pour les personnes aînées des communautés francophones en situation minoritaire (CFSM) représente un défi pour le maintien à domicile. Le but de cet article est de présenter le contexte dans lequel baignent les soins et les services à domicile, de résumer l’état des connaissances sur le sujet basé sur les travaux de l’autrice, et d’offrir un aperçu de l’avenir des soins et services à domicile. Les résultats de cette synthèse de la littérature démontrent qu’il y a très peu d’écrits portant sur le maintien à domicile en CFSM alors que les personnes aînées francophones sont plus âgées que leurs homologues anglophones. Par conséquent, les travaux de l’autrice permettent d’établir une base sur laquelle de futures initiatives peuvent s’ancrer. Quant à l’avenir des soins et services à domicile, certaines perspectives permettent d’émettre quelques idées pour l’avancement des connaissances dans le domaine. Mots-clés : vieillissement, domicile, CFSM, autonomie, services

Odds of anxiety and depression symptoms in school-aged children from official language minority communities - Dupuis, Jérémie B.; Bourque, Jimmy; El Adlouni, Salah-Eddine (Frontiers in Public Health, 2021)
Objectives: The aim of this paper is to assess the odds of suffering from anxiety or depression symptoms based on the presence of certain determinants of health for youth living in the province of New Brunswick, Canada, and in two linguistically different Official Language Minority Communities (OLMCs) in the same province. Methods: With a sample of 22,329 students from grades 7 to 12 in the province of New Brunswick, Canada, logistic regressions were performed to assess each determinant of health's effect on symptoms of anxiety and depression. Results: Some social determinants, like family support, social support and food insecurity, were identified as important determinants of mental health status regardless of linguistic group membership or community membership, while other determinants, such as alcohol use, cannabis use and natural environment, were more prominent in one OLMC than the other. Discussion: Social psychology and public health theories are used in an attempt to explain the results. Limitations and recommendations are also brought forward.

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations

Vers une culture de l’offre active de services de santé dans les deux langues officielles, étude de cas d’une pratique de dialogue. - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Tensions linguistiques au Nouveau-Brunswick : attitudes à l’égard du bilinguisme dans le système de santé. - Landry, Michelle; Legault-Leclair, Jacob; McLaughlin, Gilbert (Minorités linguistiques et société, 2024)
Dans cet article, nous examinons les opinions des anglophones à l’égard du bilinguisme dans le système de santé. Les données proviennent d’un sondage mené par la firme Léger du 16 au 24 février 2021. Nous avons mesuré l’effet d’une série de variables sociodémographiques, de l’orientation politique et de l’accord avec un énoncé selon lequel les francophones constitueraient un groupe privilégié sur le fait d’être d’avis que les services bilingues sont suffisamment développés dans le secteur de la santé. En conclusion, les résultats indiquent que les électeurs des partis politiques conservateurs et du People’s Alliance ont en majorité tendance à estimer que le bilinguisme en santé est suffisamment développé. Les variables sociodémographiques et le fait d’affirmer que les francophones représentent un groupe privilégié ne sont pas des variables discriminantes dans notre analyse. Mots-clés : Bilinguisme, Nouveau-Brunswick, système de santé, Acadie, services en français

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Le renforcement des capacités : déclin ou levier à l'amélioration de la qualité de vie des aînés ? Le cas de St-Wilfred et de Robertville en Acadie - Simard, Majella (Reflets, 2022)
Le vieillissement de la population représente une réalité complexe. Bien que les causes attribuables à ce phénomène fassent consensus auprès des chercheurs, ses manifestations et ses conséquences diffèrent d’un endroit à l’autre. Dès lors, le rythme et l’intensité du vieillissement ainsi que les moyens déployés par les différents acteurs sociaux pour en atténuer les effets et améliorer les conditions de vie des aînés se manifestent aussi différemment selon les milieux géographiques. Pour diverses raisons liées à la démographie et à la géographie, les défis liés à la gestion du vieillissement tendent à se manifester avec plus d’acuité en milieu minoritaire francophone. L’objectif de cet article consiste à examiner la contribution du modèle de renforcement des capacités à l’amélioration de la qualité de vie des aînés vivant au sein de deux localités sises en milieu rural minoritaire francophone. L’étude de cas exploratoire couplée à l’approche des représentations sociales des acteurs a été retenue comme méthode d’analyse. Des entrevues semi-dirigées effectuées auprès d’intervenants locaux et communautaires ainsi que la tenue de deux groupes de discussion constituent les instruments d’analyse qui ont été mobilisés. Bien que les résultats de notre analyse révèlent le rôle d’avant-plan de la résilience, du réseautage, de la vie relationnelle, du sentiment identitaire et du capital social dans l’amélioration de la qualité de vie des aînés, ces composantes relatives à leurs facultés s’avéreraient insuffisantes afin de favoriser un vieillissement sur place, d’où la nécessité de déployer en amont une politique territoriale du vieillissement. Mots-clés : vieillissement, milieu rural, renforcement des capacités, qualité de vie, Acadie

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)